Tuning the functional sites in metal–organic frameworks to modulate CO2 heats of adsorption. Issue 4 (4th September 2014) - Das, Anita; D'Alessandro, Deanna M.
Abstract : Tuning the functional sites in metal–organic frameworks provides one strategy to vary the CO2 adsorption properties – this highlight article provides insight into modulation of another key performance criterion, namely the isosteric heat of adsorption, and its influence on CO2 capture. Abstract : Metal–organic frameworks (MOFs) have been targeted as solid state sorbents for postcombustion carbon dioxide capture due, in part, to the enormous tunability of their structures through the incorporation of different functional sites. The isosteric heat of adsorption ( Q st ) provides one measure of the interaction of a solid sorbent with guest molecules, and has a bearing on the low pressure (<1 bar) CO2 uptake, selectivity and regenerability of a material. It is a key factor in the design of adsorbents for gas separation; however, it is sometimes overlooked in the evaluation of MOFs for CO2 capture. This highlight article draws together the impact of various functional sites on the CO2 heat of adsorption, and examines the interplay between functional sites and other factors such as competing water adsorption that influence a material's suitability for CO2 capture from industrial streams.